2013
DOI: 10.1186/1471-2164-14-393
|View full text |Cite
|
Sign up to set email alerts
|

Novel genomic approaches unravel genetic architecture of complex traits in apple

Abstract: BackgroundUnderstanding the genetic architecture of quantitative traits is important for developing genome-based crop improvement methods. Genome-wide association study (GWAS) is a powerful technique for mining novel functional variants. Using a family-based design involving 1,200 apple (Malus × domestica Borkh.) seedlings genotyped for an 8K SNP array, we report the first systematic evaluation of the relative contributions of different genomic regions to various traits related to eating quality and susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(123 citation statements)
references
References 47 publications
7
114
2
Order By: Relevance
“…To this end, a single major QTL for bitter pit susceptibility was identified which mapped to LG16 of the map developed from the cross 'Redchief' × 'X6688' associated with two SSR markers; Hi22f06 and CH05c06. The QTL identified is in a similar position to markers strongly associated with bitter pit reported by Kumar et al (2013), who used SNPs from the IRSC whole genome genotyping array developed for apple by Chagne et al (2012) to identify trait-genotype associations using a total of 1,200 seedlings where bitter pit was scored as a binomial trait, and through mapping of the SNP marker most strongly associated with bitterpit incidence in that investigation, we have demonstrated that the QTL identified in the progenies mapped here is the same QTL identified by Kumar et al (2013). Bitter pit severity has been shown to be influenced by the environment (Ferguson and Watkins 1989), and the severity of bitter pit symptoms expressed by a genotype can vary widely depending on the environmental conditions and the stage of maturity of the plant.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…To this end, a single major QTL for bitter pit susceptibility was identified which mapped to LG16 of the map developed from the cross 'Redchief' × 'X6688' associated with two SSR markers; Hi22f06 and CH05c06. The QTL identified is in a similar position to markers strongly associated with bitter pit reported by Kumar et al (2013), who used SNPs from the IRSC whole genome genotyping array developed for apple by Chagne et al (2012) to identify trait-genotype associations using a total of 1,200 seedlings where bitter pit was scored as a binomial trait, and through mapping of the SNP marker most strongly associated with bitterpit incidence in that investigation, we have demonstrated that the QTL identified in the progenies mapped here is the same QTL identified by Kumar et al (2013). Bitter pit severity has been shown to be influenced by the environment (Ferguson and Watkins 1989), and the severity of bitter pit symptoms expressed by a genotype can vary widely depending on the environmental conditions and the stage of maturity of the plant.…”
Section: Discussionsupporting
confidence: 60%
“…Whilst SNP markers, such as those of the IRSC array employed by Kumar et al (2013), have the advantage of being abundant and widely distributed throughout the genomes of eukaryotic organisms (Schlotterer 2000;Toth et al 2000) they are binary in nature, and thus contain less information than multi-allelic marker types, with reports estimating that three or more SNPs are required in a haplotype block to contain the same information as a single SSR marker at any given locus (Rafalski 2002). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations